2020
DOI: 10.1029/2020gl087679
|View full text |Cite
|
Sign up to set email alerts
|

Interannual to Decadal Response of the Indonesian Throughflow Vertical Profile to Indo‐Pacific Forcing

Abstract: The Indonesian Throughflow (ITF) inflow through the Sulawesi, Maluku, and Halmahera Seas and the ITF outflow into the eastern tropical Indian Ocean, based on reanalysis and model data, are used to investigate the interannual to decadal response of the ITF vertical profile to Indo‐Pacific forcing. The thermocline (upper 300 m) inflow, driven by the North Pacific Ocean, negatively responds to El Niño‐Southern Oscillation (ENSO) with almost no lag; while the thermocline outflow lags by 5–7 months. The sub‐thermoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 69 publications
3
22
0
Order By: Relevance
“…However, as mentioned above our results indicate that the IPO does modulate signals in the NNI box on top of ENSO, in particular in the lower layer. This would be consistent with findings by Li et al (2020) that the thermocline in Makassar Strait shows larger interannual variability with periods of 2-7 years and the subthermocline large variability on decadal time scales (.10 years). Furthermore, we find periods of higher correlations versus periods of lower correlations when performing running mean correlations with window sizes of 10 and 20 years (not shown).…”
Section: Connection To Large-scale Climate Variabilitysupporting
confidence: 93%
“…However, as mentioned above our results indicate that the IPO does modulate signals in the NNI box on top of ENSO, in particular in the lower layer. This would be consistent with findings by Li et al (2020) that the thermocline in Makassar Strait shows larger interannual variability with periods of 2-7 years and the subthermocline large variability on decadal time scales (.10 years). Furthermore, we find periods of higher correlations versus periods of lower correlations when performing running mean correlations with window sizes of 10 and 20 years (not shown).…”
Section: Connection To Large-scale Climate Variabilitysupporting
confidence: 93%
“…Previous studies (Hautala et al., 1996; Molcard et al., 1994) have suggested that more than half of the Timor Strait transport occurs in sub‐thermocline layer, where South Pacific waters contributed predominantly. The asymmetric responses of tropical North and South Pacific to climate changes suggests that the upper thermocline and sub‐thermocline of the ITF are driven by different mechanisms (M. Li et al., 2020). In addition, a recent study based on a subsurface mooring in the Savu Strait has indicated a sub‐thermocline flow from the Indian Ocean to the Indonesian Seas (Wang et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we only focus on climatological features and long‐term projected changes. However, we recognize that the SCS and MC are also modulated by tropical climate variabilities in different timescales, such as ENSO (Gordon et al., 2012; Jiang et al., 2019; Qu et al., 2004; Ramos et al., 2019), IOD (e.g., Li, Gordon et al., 2020), Pacific Decadal Oscillation (Wu, 2013), Interdecadal Pacific Oscillation (e.g., Li, Gordon et al., 2020), and Philippines‐Taiwan oscillation (Chang & Oey, 2012). Furthermore, due to the potential role of oceanic mesoscale eddies (Zhang et al., 2016), SCS transport may also change in the future.…”
Section: Summary and Future Outlookmentioning
confidence: 96%